Analisis Rantai Pemasaran Kayu Sertfikasi FSC Di Kabupaten Kulon Progo - Wiyono Wiyono; Silvi Nur Oktalina; Rochmat Hidayat (Jurnal Nasional Teknologi Terapan (JNTT), 2018)
Forest certification is a market-based policy instrument aimed to ensuring that any traded timber is legal and derived from sustainably managed forests. Forest certification is not only applied to large scale forest management but also small scale such as community forest. This study aims: (1) to know the pattern of marketing chain of certified timber; (2) to know the actors involved in the marketing of certified timber; (3) to know the marketing constrains of certified timber faced by farmers. This research was conducted at Wana Lestari Menoreh Cooperative (KWLM) in Kulon Progo Regency. KWLM is a community forest cooperative that has successfully obtained a certificate of sustainable forest management with Forest Stewardship Council (FSC) standard since 2011. Data collection is done by: (1) in-depth interviews to actors involved in marketing of certified wood; (2) observation of each stage of certified timber marketing chain; (3) study documents related to marketing chain of certified timber. Data then analyzed descriptive method. The results show that: (1) the pattern of marketing chain of certified wood is simpler than non certified timber; (2) The actors involved in the marketing chain of certified timber are farmers, harvester, cooperation, PT SOBI, wood processing industry; (3) The major constraint faced by farmers in marketing of certified timber is a payment that do not made in cash as done by non-certified timber trader.